2020
DOI: 10.3390/pathogens9110964
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Symptoms of Arboviruses in Mexico

Abstract: Arboviruses such as Chikungunya (CHIKV), Dengue (DENV), and Zika virus (ZIKV) have emerged as a significant public health concern in Mexico. The existing literature lacks evidence regarding the dispersion of arboviruses, thereby limiting public health policy’s ability to integrate the diagnosis, management, and prevention. This study seeks to reveal the clinical symptoms of CHIK, DENV, and ZIKV by age group, region, sex, and time across Mexico. The confirmed cases of CHIKV, DENV, and ZIKV were compiled from Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…The first is based on a disparate immune response between sexes to certain infections 37 , 38 . For instance, female sex has been associated with severe DENV 39 and a higher frequency of symptomatic ZIKV infections 40 . In this context, studies with mice have suggested that females are mostly affected by ZIKV 41 .…”
Section: Discussionmentioning
confidence: 99%
“…The first is based on a disparate immune response between sexes to certain infections 37 , 38 . For instance, female sex has been associated with severe DENV 39 and a higher frequency of symptomatic ZIKV infections 40 . In this context, studies with mice have suggested that females are mostly affected by ZIKV 41 .…”
Section: Discussionmentioning
confidence: 99%
“…The four main dengue virus (DENV) serotypes responsible for causing the infection are DENV-1, DENV-2, DENV-3, and DENV-4 [ 5 ]. The infection is primarily characterized by fever, nausea, rash, vomiting, and aches or pains typically behind the eyes, muscles, joints, or bones [ 6 , 7 ]. These symptoms usually last for 2–7 days [ 1 , 3 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The infection is primarily characterized by fever, nausea, rash, vomiting, and aches or pains typically behind the eyes, muscles, joints, or bones [ 6 , 7 ]. These symptoms usually last for 2–7 days [ 1 , 3 , 7 ]. Sometimes, the infection becomes severe and causes internal bleeding, resulting in dengue hemorrhagic fever (dengue with a warning sign).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arbovirus is manifested as a wide variety of clinical symptoms in the host that can range from asymptomatic or oligosymptomatic infection to even death [1,2]. During the acute phases of arboviruses such as dengue fever (DENV), chikungunya (CHIKV), and zika (ZIKV), the clinical manifestations are similar [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%